2000
DOI: 10.1152/jn.2000.83.4.1979
|View full text |Cite
|
Sign up to set email alerts
|

Composition and Topographic Organization of Signals Sent From the Frontal Eye Field to the Superior Colliculus

Abstract: The frontal eye field (FEF) and superior colliculus (SC) contribute to saccadic eye movement generation, and much of the FEF's oculomotor influence may be mediated through the SC. The present study examined the composition and topographic organization of signals flowing from FEF to SC by recording from FEF neurons that were antidromically activated from rostral or caudal SC. The first and most general result was that, in a sample of 88 corticotectal neurons, the types of signals relayed from FEF to SC were hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

32
285
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 330 publications
(321 citation statements)
references
References 91 publications
32
285
1
Order By: Relevance
“…The model thus predicts that a significant population of presaccadic cells will be found in layer V, as reported previously by Segraves and Goldberg ( 1987). More recently, Sommer and Wurtz (2000) examined cells in FEF (presumably layer V) that project to the SC. They found presaccadic cells as well as a variety of cell types whose responses were not restricted to presaccadic, movement-related activity.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…The model thus predicts that a significant population of presaccadic cells will be found in layer V, as reported previously by Segraves and Goldberg ( 1987). More recently, Sommer and Wurtz (2000) examined cells in FEF (presumably layer V) that project to the SC. They found presaccadic cells as well as a variety of cell types whose responses were not restricted to presaccadic, movement-related activity.…”
Section: Discussionsupporting
confidence: 70%
“…Their results suggest that additional signals may be processed in layer V beyond those modeled here. We have not attempted to model the FEF layer V projections to brainstem oculomotor areas (Schnyder et al, 1985), although the present model would suggest a significant presaccadic activity component in this projection, which could be -32-investigated using the method of Sommer and Wurtz (2000).…”
Section: Discussionmentioning
confidence: 93%
“…It is clear that this network is essential for spatial attention during unpredictable saccade generation (Campana, Cowey, Casco, Oudsen, & Walsh, 2007) and mediating search strategies (Lane, Smith, Schenk, & Ellison, 2012), however the role of PPC -FEF network in predictable tasks in pursuit is less clear. Further evidence shows modulation of activity during single predictable saccades in FEF during single-unit recordings in monkeys (Sommer & Wurtz, 2000). The present study has shown that an area related to medial FEF or lateral SEF is important in oculomotor learning (both pursuit and saccades) of sequences of movements, and importantly, we have found the pattern of activity within these regions hold the key to this learning mechanism.…”
Section: Multivariate Analysissupporting
confidence: 69%
“…Our effects could thus have resulted from direct antidromic stimulation of neurons forming connections with the FEF, rather than from activation of neurons within the FEF, and the subsequent activation of structures to which the FEF projects. Although antidromic activation typically requires current levels greater than that used here (median ϭ 10 A) (20,21), we cannot rule out the contribution such activation may have made to our results. Moreover, the FEF is heavily interconnected with other cortical and subcortical structures, such as the superior colliculus and the lateral intraparietal area (LTP) (22), both of which are known to be involved in oculomotor behavior and spatial attention (13, [23][24].…”
Section: Discussionmentioning
confidence: 84%